2006
DOI: 10.1016/j.asieco.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

China and India: Income inequality and poverty north and south of the Himalayas

Abstract: China and India are the most populous countries of the World and also the two largest contributors to World poverty as assessed by the World Bank. This paper, focusing on the rural circumstances is the first study using microdata to compare income inequality and poverty in the two countries. We find that at the mid-1990s income inequality in rural China and rural India were relatively similar.Our results show that differences in mean income across regions are much larger in China than in India and accounts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The poverty condition in the districts/cities of Aceh Province indicates that there is an inequality in income between these regions. Several previous studies have examined the relationship between income inequality and poverty (Borooah, Gustafsson, and Li, 2006), (Farzanegan and Habibpour, 2017) which concluded that if income inequality (Gini ratio decreases, the poverty rate also decreases).…”
Section: 22mentioning
confidence: 99%
“…The poverty condition in the districts/cities of Aceh Province indicates that there is an inequality in income between these regions. Several previous studies have examined the relationship between income inequality and poverty (Borooah, Gustafsson, and Li, 2006), (Farzanegan and Habibpour, 2017) which concluded that if income inequality (Gini ratio decreases, the poverty rate also decreases).…”
Section: 22mentioning
confidence: 99%
“…If there is a dark lining to these extraordinary achievements, it is the widening income gap across the country [4]. China's recent experience provides an excellent case to study the impacts of market-oriented reforms on income distribution and income inequality in many other countries experiencing rapid urbanization and economic transition [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Farmers with more productive cropland have the potential to earn more returns and are less likely to fall into poverty (Borooah, Gustafsson, & Li, 2006;Huang, Rozelle, Lohmar, Huang, & Wang, 2006). Minority people in China usually live in regions with geographical features characterized by mountains, hills, plateaus, and deserts.…”
Section: Natural Capital and Income Inequalitymentioning
confidence: 99%